(untitled) (Applied Biological Research, 2016)
Present study was aimed to assess the effects of diet supplemented with or without enzyme treated 0.5% dandelion (Taraxacum officinale) leaves (DL) or/and 1% fenugreek (Trigonella foenum graecum) seeds (FS), fed for 42 days on gut microflora of broiler chicken. Cobb chicks (273) were randomly distributed into 7 groups with 13 chicks in each replicate treatment. Birds in control were fed with only basal diet. The study revealed that caecal total viable and coliform counts were significantly (p<0.05) low in birds fed with supplemented diets as compared to control with least population of 7.05±0.03 and 4.07±0.05 cfu g-1, respectively, in chicken fed with enzyme treated 0.5% DL + 1% FS basal diet. The pH and moisture content of chicken litter showed no significant variation amongst the treatments. Both DL and FS showed beneficial health effects in terms of reducing the harmful gut bacteria.